Effects of Al content on microstructure of as-cast Mg–3·5Ca alloy. (July 2014) - Jiang, Z. T.; Jiang, B.; Xiao, Y.; Tian, Y.; Zhou, G. Y.; Pan, F. S.
Abstract : Mg– x Al–3·5Ca ( x  = 0, 1, 2·5, 5 and 7·5, wt-%) alloys were prepared, and the effects of Al content on the microstructures of the as cast Mg–3·5Ca were investigated. The results showed that with increasing of the Al content, second phase evolution sequences are Mg2 Ca→(Mg, Al)2 Ca→Al2 Ca+Mg17 Al12 . And the morphology transformation process of the phases formed along the interdendritic regions in as cast alloys was from a fine granular shape, a lamella type to thick bone with Al addition. These changes associate with an increase in the Al content and the Ca/Al ratio. With increasing of Al content in Mg–3·5Ca alloy, the mean grain size has a trend of first decrease and then increase, which is mainly caused by the constitutional undercooling as well as the changes of the distribution and morphology of the phases at as cast state.